Genome-wide regulatory dynamics of translation in the Plasmodium falciparum asexual blood stages - Florence Caro; Vida Ahyong; Miguel Betegon; Joseph L DeRisi (eLife, 2014)
The characterization of the transcriptome and proteome of Plasmodium falciparum has been a tremendous resource for the understanding of the molecular physiology of this parasite. However, the translational dynamics that link steady-state mRNA with protein levels are not well understood. In this study, we bridge this disconnect by measuring genome-wide translation using ribosome profiling, through five stages of the P. falciparum blood phase developmental cycle. Our findings show that transcription and translation are tightly coupled, with overt translational control occurring for less than 10% of the transcriptome. Translationally regulated genes are predominantly associated with merozoite egress functions. We systematically define mRNA 5′ leader sequences, and 3′ UTRs, as well as antisense transcripts, along with ribosome occupancy for each, and establish that accumulation of ribosomes on 5′ leaders is a common transcript feature. This work represents the highest resolution and broadest portrait of gene expression and translation to date for this medically important parasite.